IMPROVING THE TAX SYSTEM IN THE DEVELOPMENT OF TOURISM ORGANIZATIONS - Irgashev Tulkun Isergapovich (Ecomind Press, 2025)
This article analyzes the issues of improving the tax system in the process of developing the tourism sector in the Republic of Uzbekistan. The study examines ways to increase the financial stability of tourism organizations, simplify taxation mechanisms, and enhance investment attractiveness. The author has developed proposals aimed at increasing the competitiveness of the sector through tax breaks, incentives, and digital tax management in tourism.
Keywords: Tourism economy, tax system, incentives, tourism organizations, investment climate.